PENGADAAN AIR BERSIH DALAM MEMBANGUN ADAPTASI KEBIASAAN BARU DALAM MEMBANGUN POLA HIDUP BERSIH DAN SEHAT ( UPAYA MEMUTUS MATA RANTAI WABAH COVID 19) - Iwan Satriyo Nugroho, Iwan Satriyo Nugroho; Darwin Nahwan, Darwin Nahwan; Moch Irwan Hermanto, Moch Irwan Hermanto; Budiman Fauzi, Budiman Fauzi; Muhajirin, Muhajirin; Musyfiq Amrullah, Musyfiq Amrullah; Riko Darma Putra, Riko Darma Putra (Media Nusantara, 2021)
The government has formed a Task Force for Handling Covid 19 followed by the formation of a Handling Committee. In Indonesia to break the chain of the Covid 19 epidemic, the government has implemented a Large-Scale Social Restrictions (PSBB) policy based on Minister of Health Regulation Number 9 of 2020. PSBB is a restriction on public activities in public places and quarantine yourself at home. The activity restrictions implemented include school closures, workplaces, religious restrictions and restrictions on other activities in public places. The PSBB was continued with the Adaptation of New Habits (AKB) which was implemented in several parts of Indonesia, including West Java Province. Adapting new habits such as using masks, continuing to study and work at home, maintaining distance, washing hands, maintaining personal and environmental hygiene, and maintaining a healthy lifestyle, are new patterns of life for society that must continue to be carried out and become habits forever. All efforts are being made to break the chain of the Covid 19 outbreak. However, everything will not go according to plan if it is not supported by the entire community, especially higher education institutions as the front guard in building awareness and real activities in breaking the chain of this epidemic.